2019
DOI: 10.35826/ijoess.2599
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Support and the Role of Organizational Trust in Employee Empowerm

Abstract: In this study, the relationship between organizational support, organizational trust and personnel empowerment was examined. In order to determine this relationship, a questionnaire was applied to the employees in a production company. The data obtained were interpreted by means of SPSS package program. In the first part of the study, literature review was conducted to explain the concepts of organizational support, organizational trust and empowerment. In the second part, the relationship between organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…The findings showed that organizational trust is critical for PAS indicating that the relationship is positive and the increase in organizational trust will result in a positive increase in the PAS in Jordan. Having a high level of organizational trust will lead to a positive increase in the performance of employees as shown in various findings of previous studies (Jiang & Chen, 2017;Naami & Hashemi, 2020;Sharkie, 2009;Yılmaz, 2019).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The findings showed that organizational trust is critical for PAS indicating that the relationship is positive and the increase in organizational trust will result in a positive increase in the PAS in Jordan. Having a high level of organizational trust will lead to a positive increase in the performance of employees as shown in various findings of previous studies (Jiang & Chen, 2017;Naami & Hashemi, 2020;Sharkie, 2009;Yılmaz, 2019).…”
Section: Discussionmentioning
confidence: 65%
“…The increase in vulnerability has increased the role of trust in the working environment (Sharkie, 2009). Organizational trust has a significant positive effect on employee empowerment (Yılmaz, 2019). The study of Jiang and Chen (2017) found a positive effect of organizational trust in organizational learning and creativity among employees in high-tech industries in China.…”
Section: Trust and Pasmentioning
confidence: 99%
“…Kepercayaan telah dipertimbangkan sebagai katalis dalam berbagai transaksi antara penjual dan pembeli agar kepuasan konsumen dapat terwujud sesuai dengan yang diharapkan. Menurut Deutsch (dalam Yilmaz dan Atalay, 2009).…”
Section: Pengaruh Kepercayaan Terhadap Minat Bertransaksi Menggunakan...unclassified
“…-The effect of virtual interactions on the relationship between trust and organizational commitment Based on the literature, trust facilitates open communication, information sharing, job satisfaction, and organizational commitment. Yilmaz and Atali (2009) [23] stated that trust has a positive effect on organizational commitment and improving social relationships. Because of the high level of uncertainty in virtual structures, the existence of trust is essential for its survival, the higher the level of trust, and the lower the uncertainty.…”
Section: Theoretical Foundations and Hypotheses -Virtual Interactions...mentioning
confidence: 99%